2015
DOI: 10.5194/bg-12-345-2015
|View full text |Cite
|
Sign up to set email alerts
|

Lena Delta hydrology and geochemistry: long-term hydrological data and recent field observations

Abstract: Abstract. The Lena River forms one of the largest deltas in the Arctic. We compare two sets of data to reveal new insights into the hydrological, hydrochemical, and geochemical processes within the delta: (i) long-term hydrometric observations at the Khabarova station at the head of the delta from 1951 to 2005; (ii) field hydrological and geochemical observations carried out within the delta since 2002. Periods with differing relative discharge and intensity of fluvial processes were identified from the long-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 27 publications
4
67
0
3
Order By: Relevance
“…Much of the Chukchi and Beaufort seas' coastlines are similarly ice-rich and can be expected to be subject to the same mechanisms of geomorphologic change in response to shifts in environmental drivers of coastal dynamics (Ping et al, 2011). Regionally, relevant shifts in the energy and water balances at the land-atmosphere interface (Boike et al, 2013), increases in Lena River discharge (Fedorova et al, 2015) and increases in the duration of open water and coastal erosion (Günther et al, 2015) have recently been observed, matching similar circumpolar observations (Barnhart et al, 2014).…”
Section: Study Areasupporting
confidence: 64%
“…Much of the Chukchi and Beaufort seas' coastlines are similarly ice-rich and can be expected to be subject to the same mechanisms of geomorphologic change in response to shifts in environmental drivers of coastal dynamics (Ping et al, 2011). Regionally, relevant shifts in the energy and water balances at the land-atmosphere interface (Boike et al, 2013), increases in Lena River discharge (Fedorova et al, 2015) and increases in the duration of open water and coastal erosion (Günther et al, 2015) have recently been observed, matching similar circumpolar observations (Barnhart et al, 2014).…”
Section: Study Areasupporting
confidence: 64%
“…The study site is located in a riverine environment without marine wave activity, about 10 km inland from the outer delta margins. The annual average water discharge of the Olenekskaya channel shows strong annual variations ranging from 700 to 1.500 m 3 /s [43] and open water conditions exist from June to October. The water levels during spring river ice break-up in late May to early June can reach up to 12 m above normal at this location but does not exceed the upper limit of the sand unit (Figure 1c).…”
Section: Study Areamentioning
confidence: 99%
“…Despite such small-scale variability, the LRD can be classified in three main geomorphological units (Fig. 1), which have distinctly different characteristics regarding their surface and subsurface properties, such as ground ice contents, thermokarst features and vegetation cover (Morgenstern et al, 2013;Fedorova et al, 2015).…”
Section: The Lena River Deltamentioning
confidence: 99%